A study of employee well-being in the Kingdom of Bahrain - Moovala, Vijayalaxmi (Advances in Social Sciences Research Journal, 2021)
Organisations are investing in employee well-being initiatives, as employees constitute the most important stakeholder group. Employee well-being requires a focused and concentrated approach. The main aim of this study was to assess the importance of employee well-being in organisations in the Kingdom of Bahrain. The study was based on the five domains of employee well-being model [1]. The five domains being the health domain, the work domain, the values/principles domain, the collective/social domain, and the personal growth domain. The study revealed that majority of the participating organisations were focusing more on factors related to physical health and physical safety of their employees than on mental health. Significant factors like pay and rewards, autonomy, job satisfaction, people management policies, professional management, workload distribution, and leadership need improvement when compared to factors like work-life balance, open and inclusive work environment. All these factors relate to the work domain. In the values/principles domain, more participating organisations had a clear mission and objectives, and were investing in training their managers and employees, whereas ethical standards, diversity and inclusion, cultural engagement, corporate governance, corporate social responsibility, dignity at work and mutual trust at the workplace, needs to be given more attention. Very few participating organisations have value-based leadership and a well-being strategy in place. Teamworking, dignity and respect at the workplace were evident in more participating organisations than factors like positive and healthy relationships, employee voice, supportive management style. All these factors contribute to the collective/social domain of employee well-being, In the personal growth domain, performance management and personal development plans, open and collaborative culture, and succession planning were prevalent in more participating organisations than effective utilisation of employees’ skills, coaching and mentoring, resilience training, positive emotional relationships, financial well-being, challenging work , lifelong learning, access to training and creativity. Mid-career review was conspicuous by its absence in all participating organisations. The study reveals that employee well-being in organisations in the Kingdom of Bahrain needs more attention and focus than what is being accorded now.